CORRELATION BETWEEN VISUAL IMPROVEMENT AND BEHAVIOR OF SANITATION MANAGEMENT IN KAMPUNG CODE, YOGYAKARTA - - NIM. 25717009, Windini
According to the Ministry of Public Works, the provision of decent sanitation access to slums reaches only 10% of total slums in Indonesia, with total number of slums in Indonesia by 2017 reaching 7.6 million homes. These condition need specific approach strategies to be able to improve decent sanitation access especially in urban slums, especially on riverbanks. One of the economic stategies and able to raise public awareness of the importance of sanitation is to change the visual appearance of the slum buildings into colorful. This study aims to determine the correlation between visual improvment and sanitation behavior, as measured by domestic wastewater management behavior and waste management behavior. This research uses a non- experimental quantitative approach with correlational research design. Data processing is done by using parametric statistical method. The dependent variables in this research is wastewater management behavior and solid waste management behavior, while the independent variable in this research is attitude, subjective norm, and perceived behavioran control while visual improvment is part of perceived behavioral control variable. Each variable has interval measurement scale. The statistical test method used is Path Analysis. With the confidence interval of 99% and a population of 64 households, the sample size obtained based on the Slovin formula is 64 households, so the sampling technique is total sampling. The measuring tool used is a questionnaire that is designed based on the Theory of Planned Behavior that uses a Likert scale. The questionnare is designed based on the Theory of Planned Behavior. Validity test is done by content validity method and reliability test is done by calculating CronbachÃ‚Â’s Alpha using SPSS version 21. The results of this study is state that there is significant correlation between visual improvement and domestic wastewater management behavior and solid waste management behavior.